Tilapia (Oreochromis niloticus) as a biondicator of copper and cadmium toxicity. A bioavailability approach - Silva, Maria A.; Motta, Tatiana C. S.; Tintor, Diogo B. [UNESP]; Dourado, Thiago A. [UNESP]; Alcântara, Amanda L. [UNESP]; Menegário, Amauri A. [UNESP]; Ferreira, José R. (Sociedade Brasileira de Quimica (SBQ), 2017)
The acute toxicity of copper and cadmium in Oreochromis niloticus was evaluated through a 96 h static assay. Precipitation of Cu and co-precipitation of Cd in the presence of Cu were noted, being indicative of differences in nominal and actual concentrations of metals. Under these conditions, LC50-96h was determined as 3.53 mg L-1 Cu, 20.1 mg L-1 Cd and 1.36 mg L-1 (Cu + Cd). Besides the quantitative determinations of total dissolved metals in water, considerations on Cd/Cu interactions in aquatic media were presented, allowing the assessment for metals speciation. Data revealed that alkalinity, hardness, dissolved organic carbon and formation of inorganic complexes reduce metal availabilities, mainly in relation to Cu. In spite of this, the LC50 for Cd was significantly reduced in the presence of Cu, matching environmental realistic values. Based on simulated fate of metals, hardness may impair a reduction of 18 and 2% in metal activities, respectively to Cu and Cd.
Keywords: Bioavailability; Bioindicator; Chemical speciation; Metals acute toxicity; Oreochromis niloticus